ضمانات حماية المستهلك في قانون المنافسة - عثمان خليفي; عصام بوصايري (My University, 2020)
summary This study dealt with the subject of guarantees established for consumer protection under the competition law, and two types of guarantees were discussed, namely preventive guarantees and deterrent guarantees . Regarding preventive guarantees, which aim to highlight the role of the legislator in protecting the consumer, and his tireless attempts in this regard, through a set of legal rules scattered between the successive competition laws, especially the amended and supplemented Order 03-03, as well as the complementary laws such as the rules applied to commercial practices under Law 04 - 02 amended and supplemented, as well as consumer protection laws, especially Law 09-03 amended and supplemented, which stipulated the violations and practices that must be prohibited in order to achieve consumer protection, either directly or indirectly . As for deterrent guarantees, which refers to the set of legal mechanisms and means available to protect consumers on the ground, they have been addressed through the regulatory agencies and their role in the embodiment and implementation of the aforementioned laws, including the Competition Council and the Ministry of Commerce mainly, as well as local groups in a secondary way. Then the role of other bodies in the field of deterrent protection, even in an injurious manner, was discussed, such as consumer protection associations, which are considered one of the most effective means by which consumers are guaranteed the collective defense of their interests, as well as the specialized judicial authorities, as the Algerian legislator approved the consumer legal protection in the penal code, and granted it The right to the possibility of resorting to the judiciary when there are elements and causes that have led to harm it as a result of the commercial and contractual dealings that it enters into in the field of consumption, and this is given the powers vested in the judicial organs in the framework of searching for various crimes in general and economic crimes in particular . ................... الملخص تناولت هذه الدراسة موضوع الضمانات المقررة لحماية المستهلك في ظل قانون المنافسة، وقد تم التطرق فيها إلى نوعين من الضمانات وهما الضمانات الوقائية، والضمانات الردعية. فبالنسبة للضمانات الوقائية والتي تهدف إلى إبراز دور المشرع في حماية المستهلك، ومحاولاته الحثيثة في هذا الصدد، من خلال مجموعة من القواعد القانونية المتناثرة بين قوانين المنافسة المتعاقبة لاسيما الأمر 03-03 المعدل والمتمم، وكذا القوانين المكملة لها كالقواعد المطبقة على الممارسات التجارية بموجب القانون 04-02 المعدل والمتمم، وكذا قوانين حماية المستهلك لاسيما القانون 09-03 المعدل والمتمم، والتي نصت على المخالفات والممارسات التي يجب حظرها للوصول إلى حماية للمستهلك سواء بطريقة مباشرة أم غير مباشرة. أما بالنسبة للضمانات الردعية والتي يقصد بها مجموعة الآليات والوسائل القانونية المتوفرة لحماية المستهلك على أرض الواقع، فقد تم تناولها من خلال الأجهزة الرقابية ودورها في تجسيد وتطبيق القوانين سابقة الذكر، ومنها مجلس المنافسة ووزارة التجارة بشكل أساسي، وكذا الجماعات المحلية بصورة ثانوية. ثم تم التطرق لدور أجهزة أخرى في مجال الحماية الردعية ولو بصفة زجرية، مثل جمعيات حماية المستهلك التي تعتبر من أنجع الوسائل التي من خلالها يضمن للمستهلكين الدفاع الجماعي عن مصالحهم، وكذا الجهات القضائية المتخصصة، حيث أقر المشرع الجزائري للمستهلك حماية قانونية في قانون العقوبات، ومنحه الحق في إمكانية اللجوء إلى القضاء وذلك متى توافرت عناصر وأسباب أدت إلى الإضرار به من جراء التعاملات التجارية والتعاقدية التي يبرمها في مجال الاستهلاك، وهذا بالنظر إلى الصلاحيات المخولة للأجهزة القضائية في إطار البحث عن مختلف الجرائم عموما والجرائم الاقتصادية خصوصا . ........................ Résumé Cette étude portait sur les garanties établies pour la protection des consommateurs en vertu du droit de la concurrence, dans lesquelles deux types de garanties ont été abordées : les garanties et les garanties dissuasives. Pour des garanties visant à mettre en évidence le rôle du législateur dans la protection des consommateurs et ses efforts inlassables à cet égard, à travers un ensemble de règles juridiques dispersées entre les lois successives sur la concurrence, notamment l’ordonnance 03-03 modifié et complété ainsi que les lois complémentaires telles que les règles applicables aux pratiques commerciales en vertu de la loi 04-02 modifiée et complétée, Ainsi que les lois sur la protection du consommateur, en particulier la loi 09-03, modifiant et complétant, qui stipule les violations et les pratiques qui doivent être interdites pour obtenir directement ou indirectement la protection des consommateurs. Quant aux garanties dissuasives, qui sont conçues comme un ensemble de mécanismes juridiques et de moyens disponibles pour la protection des consommateurs sur le terrain, elles ont été abordées par les organismes de réglementation et leur rôle dans la traduction et l’application des lois susmentionnées, principalement le Conseil de la concurrence et le ministère du Commerce, ainsi que par les communautés locales. Le rôle des autres organismes de protection dissuasive a ensuite été abordé, même dans le cadre d’une injonction. ", tels que les associations de protection des consommateurs, par lesquelles les consommateurs sont assurés de la défense collective de leurs intérêts, ainsi que les organes judiciaires spécialisés, la législation algérienne des consommateurs a affirmé la protection juridique dans le Code pénal. Le droit d’accès à la justice est accordé lorsqu’il existe des éléments et des causes de préjudice qui lui sont causés par ses relations commerciales et contractuelles dans le domaine de la consommation dans la recherche de divers crimes en général et de crimes économiques en particulier.